Transformation of Islamic Religious Education Teaching Materials Based on HOTS and Religious Moderation - Amin, Khairul; Nasution, Juni Erpida (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to analyze and transform Islamic Religious Education (PAI) teaching materials based on HOTS and religious moderation as a strategy for building adaptive, inclusive, and digitally literate Islamic character. The research method uses a qualitative-descriptive approach through interviews, observations, and document analysis at two PTKIS (Islamic Higher Education Institutions) in Pekanbaru. The results show that the implementation of HOTS-based learning activities, such as problem-based learning, digital collaboration, and contextual case studies, combined with the values of tolerance, justice, and balance, can increase critical awareness and moral reasoning of students. The transformation of Islamic Religious Education (PAI) teaching materials based on HOTS and religious moderation not only strengthens the relevance of Islamic education in the digital era but also contributes to the formation of a generation of faithful, knowledgeable, and moderate morals. Thus, this study emphasizes the need for transformation of the curriculum, learning strategies, and pedagogical competencies of Islamic Religious Education lecturers.